2012
DOI: 10.5301/jn.5000104
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the incidence of intestinal perforation in US dialysis patients (1992-2005)

Abstract: Background Little is known about the incidence of intestinal perforation in patients undergoing dialysis. Concerns exist that sevelamer hydrochloride may increase the risk of intestinal perforation. We examined long-term trends for the incidence of intestinal perforation among US dialysis patients. Methods We studied all dialysis patients (1992–2005) who had Medicare as primary payer. We used ICD-9 diagnosis code 569.83 to ascertain events of intestinal perforation. We studied (a) all perforations and (b) pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…It has been reported that patients on hemodialysis have a high risk of colonic perforation even without sevelamer administration, and there were no significant changes in the incidence of bowel perforation after the approval of sevelamer ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that patients on hemodialysis have a high risk of colonic perforation even without sevelamer administration, and there were no significant changes in the incidence of bowel perforation after the approval of sevelamer ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Yang JY revealed that the incidence of intestinal perforation in the United States between 1992 and 2005 was approximately 0.4%. The 30-day mortality rates following intestinal perforation were reported to be 42.3% for all cases of intestinal perforation ( 6 ). In our analysis of cases over the past decade involving PD complicated by visceral perforation, we identified 18 reported instances in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…If sevelamer is not stopped, complications such as ischemia, ulceration, acute anemia, stricture formation, and perforation may occur. [1][2][3][4][5][6]…”
Section: Discussionmentioning
confidence: 99%